Opportunities and Threats of ASEAN Economic Community for Micro, Small and Medium Enterprises in East Java - Rizki Rahmadini Nurika (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
The implementation of the ASEAN Economic Community (AEC) in 2015 is aimed to improve economic relations in ASEAN. The AEC required provisions for the trade liberalization that might impact positively or negatively for entrepreneurs. This article is aimed to describe the opportunities and threats of AEC for Micro, Small and Medium Enterprises (MSMEs) in East Java. If AEC has been implemented for more than five years, AEC should have made a real contribution to MSMEs in East Java. In fact, there were many MSMEs in East Java who don't even know what AEC is. To analyze it, the author used the concept of economic integration by Bela Balassa. The author used a type of descriptive research with a qualitative approach. The data used in this study are primary and secondary data. Based on the findings, the opportunities for AEC for MSMEs in East Java are product standardization and market access. Meanwhile, AEC's threats to them are product similarity, foreign investment, and the free flow of goods. Even so, both do not have a significant impact on MSMEs in East Java because the target sales of MSMEs in East Java are mostly for the domestic market.